2016
DOI: 10.1002/hep.28418
|View full text |Cite
|
Sign up to set email alerts
|

Histidine‐rich glycoprotein promotes macrophage activation and inflammation in chronic liver disease

Abstract: Pathogen-and injury-related danger signals as well as cytokines released by immune cells influence the functional differentiation of macrophages in chronic inflammation. Recently, the liver-derived plasma protein, histidine-rich glycoprotein (HRG), was demonstrated, in mouse tumor models, to mediate the transition of alternatively activated (M2) to proinflammatory (M1) macrophages, which limit tumor growth and metastasis. We hypothesized that liver-derived HRG is a critical endogenous modulator of hepatic macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 37 publications
6
85
0
Order By: Relevance
“…Bartneck et al. () have found that His‐rich glycoprotein promoted macrophage activation and inflammation in mouse models. For example, His‐rich glycoprotein appears to be an endogenous molecular factor promoting the polarization of hepatic macrophages toward the proinflammatory phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Bartneck et al. () have found that His‐rich glycoprotein promoted macrophage activation and inflammation in mouse models. For example, His‐rich glycoprotein appears to be an endogenous molecular factor promoting the polarization of hepatic macrophages toward the proinflammatory phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…The NAFLD activity score was assessed by an expert pathologist (T. Longerich) who was blinded to the treatment group. Immunohistochemistry for F4/80 (Abcam) was performed on paraffin‐embedded liver sections and indirect immunofluorescence staining with collagen‐1 antibody (Novus Biologicals, Germany) on liver cryosections, both according to standard protocols . Hepatic leukocytes were analyzed by multicolor flow cytometry using an LSR‐Fortessa (BD Biosciences), as described …”
Section: Methodsmentioning
confidence: 99%
“…2,3 Persistent and excessive activation of macrophages results in pathological inflammation and fibrosis in chronic liver diseases. [4][5][6][7] Previous research suggests that activated macrophages are present in portal infiltrates and at sites of interface hepatitis in AIH. [8][9][10][11] Nonetheless, until now little has been known about the molecular mechanisms of macrophage activation in AIH.…”
Section: Introductionmentioning
confidence: 99%